Efektivitas Program Layanan E-KLAMPID di Kecamatan Bulak Kota Surabaya - Mirza Fatchul Haqq; Sri Umiyati (Public Sphere Review, 2022)
In an effort to realize an effective and efficient public service department of Population and Civil Registry Surabaya made a public service innovation that is E-klampid Program. This Program aims to facilitate the community in conducting the management of population and civil registration, people no longer need to come to the Office Dispendukcapil Surabaya, and e community can do the management independently at home this study aims to analyze the effectiveness of e-klampid program in District Bulak Surabaya. This study uses dea scriptive qualitative method with a case study approach, the existence of e-klampid can provide convenience for the community in managing population and civil registration. Sources of data used are secondary data and primary data obtained through interviews, observation and documentation. There are 5 indicators in measuring the effectiveness of the Program according to Sutrisno (2007), namely 1) Understanding The Program 2) right on target 3) On Time 4) achievement of goals 5) real change. The results showed that the effectiveness of the e-klampid Program in Bulak Sub-District of Surabaya has not been effective. There are 4 indicators that are not effective, namely understanding the Program, right on target, achieving goals, Real Change. The effective indicator is timely.